2011
DOI: 10.1586/ecp.11.5
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of Toll-like receptor agonists and the impact on the immune system

Abstract: Toll-like receptor (TLR) ligation activates both the innate and adaptive immune systems, and plays an important role in antiviral and anti-tumor immunity. Therefore, a significant amount of effort has been devoted to exploit the therapeutic potential of TLR agonists. Depending on the therapeutic purpose, either as adjuvants to vaccine, chemotherapy or standalone therapy, TLR agonists have been administered via different routes. Both preclinical and clinical studies have suggested that the route of administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
147
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(154 citation statements)
references
References 114 publications
3
147
1
3
Order By: Relevance
“…administration of SD-101 generated adaptive antitumor immunity (30). Recent reports indicate a few safety concerns after the systemic administration of TLR agonists (42), including lymphopenia and flu-like symptoms (65). A repeated systemic administration of TLR agonists can also induce a state of immune unresponsiveness, known as TLR tolerance (Supplemental Figure 10B) (66).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…administration of SD-101 generated adaptive antitumor immunity (30). Recent reports indicate a few safety concerns after the systemic administration of TLR agonists (42), including lymphopenia and flu-like symptoms (65). A repeated systemic administration of TLR agonists can also induce a state of immune unresponsiveness, known as TLR tolerance (Supplemental Figure 10B) (66).…”
Section: Discussionmentioning
confidence: 99%
“…administration of TLR7 and TLR9 agonists. Cytokine release syndrome is a serious adverse effect of immunotherapies, including therapies with TLR agonists (42). To evaluate systemic proinflammatory cytokine production after treatment, serum samples were collected on day 13 for 1V270 and on day 12 for SD-101 ( Figure 1, G-J).…”
Section: Combination Therapy With It Tlr Agonists and Systemic Antimentioning
confidence: 99%
“…Pharmacokinetic studies in rodents showed that phosphorothioate bonds oligonucleotides injected i.v. display an elimination half-life of 25 to 50 hours, with the majority of the drug taken up by the liver and kidney (44 …”
Section: Discussionmentioning
confidence: 99%
“…This score indicates that there is a greater inflammatory response when AR-12 is administered to an infected mouse than an uninfected mouse and highlights the potential benefit of using AR-12 in a manner similar to that for many adjunctive immunomodulatory compounds. However, in contrast to several of these compounds, such as Toll-like receptor (TLR) agonists (42), AR-12/MPs do not appear to have significant toxicities, even when the host is not infected. A more comprehensive evaluation of the potential adverse effects of the drug in vivo is planned for future experiments.…”
Section: Discussionmentioning
confidence: 99%